(untitled) (Context: Journal of Interdisciplinary Studies, 2022)
Integrating religion into everyday life is the goal of every believer wherever they are, including the diasporic context. When recognizing and anticipating the challenges of the diasporic Muslim community of the Western Balkan origin, the experience of those who live what we consider a religious diasporic life for a long period of time can certainly help. The purpose of presenting challenges and analysing their impact on the religious practice and the lives of religious community members is to anticipate the development of these challenges and search for ways to enhance organization of the religious life, as well as help religious community members to fulfil their religious needs.